The unreality of evil - Mander, W (Springer Verlag, 2017)
The simplest response to the problem of evil is to deny that there exists any evil, but that answer is usually dismissed as obviously unacceptable. This paper takes issue with that assessment and argues that it is an answer deserving of serious consideration. After rejecting four manifestly unacceptable formulations, two further conceptions are identified—the ‘higher standard’ and ‘wider perspective’ answers—which merit closer attention. The remainder of the paper considers and responds to four main objections to the theory: that it runs contrary to our experience, that it is self-defeating, that it makes a nonsense of worship and that it would undermine moral action.